Increased longevity due to sexual activity in mole-rats is associated with transcriptional changes in the HPA stress axis - Sahm, Arne; Platzer, Matthias; Koch, Philipp; Henning, Yoshiyuki; Bens, Martin; Groth, Marco; Burda, Hynek; Begall, Sabine; Ting, Saskia; Goetz, Moritz; Van Daele, Paul; Staniszewska, Magdalena; et al. (eLife, 2021)
Sexual activity and/or reproduction are associated with a doubling of life expectancy in the long-lived rodent genus Fukomys. To investigate the molecular mechanisms underlying this phenomenon, we analyzed 636 RNA-seq samples across 15 tissues. This analysis suggests that changes in the regulation of the hypothalamic-pituitary-adrenal stress axis play a key role regarding the extended life expectancy of reproductive vs. non-reproductive mole-rats. This is substantiated by a corpus of independent evidence. In accordance with previous studies, the up-regulation of the proteasome and so-called 'anti-aging molecules', for example, dehydroepiandrosterone, is linked with enhanced lifespan. On the other hand, several of our results are not consistent with knowledge about aging of short-lived model organisms. For example, we found the up-regulation of the insulin-like growth factor 1/growth hormone axis and several other anabolic processes to be compatible with a considerable lifespan prolongation. These contradictions question the extent to which findings from short-lived species can be transferred to longer-lived ones.
Keywords: zvířata; Gene Expression; Female; Male; systems biology; Fukomys; Mole Rats; dlouhověkost; Longevity; Dehydroepiandrosterone; gene expression; Animals; Stress, Psychological; mužské pohlaví; computational biology; rozmnožování; Insulin-Like Growth Factor I; ženské pohlaví; hypothalamic-pituitary-adrenal axis; Hypothalamo-Hypophyseal System; Pituitary-Adrenal System; Reproduction; lifespan; mikroftalmičtí podzemní hlodavci; differential gene expression; Sexual Behavior, Animal; ACTHR; exprese genu; chromosomes; insulinu podobný růstový faktor I; DHEA; sexuální chování zvířat; systém hypotalamus-hypofýza; psychický stres; dehydroepiandrosteron; systém hypofýza - nadledviny